Microenvironment‐Adaptive Nanozyme for Accelerating Drug‐Resistant Bacteria‐Infected Wound Healing. Issue 10 (16th January 2023) - Yu, Lei; Sun, Yiping; Niu, Yusheng; Zhang, Pengfei; Hu, Jun; Chen, Zhong; Zhang, Gong; Xu, Yuanhong
Abstract: Reactive oxygen species (ROS) are favorable for antibacterial infection but their overproduction results in serious inflammatory response and aggravates the hypoxic state of the wound tissue, which is detrimental to healing stages of proliferation and remodeling. Here, an atomic‐dispersion Fe‐doped oxygen‐deficient molybdenum oxide MoO3− X (ADFM) bifunctional nanozyme, featuring implanted peroxidase‐like and enhanced catalase‐like activity, is developed for decomposing H2 O2 into strongly oxidizing hydroxyl radicals (OH) for prevention of bacterial infection and into plentiful O2 for healing stages. Therein, the introduction of Fe into MoO3− X primarily produces an asymmetric electron density difference by elongating the bond length between metal atoms, synchronously stabilizing adsorption of OH and weakening the adsorption of O2 . ADFM also shows unimaginably high aqueous dispersity and pH‐adaptive ROS regulation in the wound microenvironment, both of which are favorable for ADFM to fully exert enzyme‐like activity for timely antibacterial and efficient wound‐healing action. ADFM thus achieves efficient healing of drug‐resistant bacteria‐infected wounds in vivo, at an ultralow dosage of 30 µg mL −1 against 10 6 CFU mL −1 extended spectrum β ‐lactamases‐producing Escherichia coli, exhibiting a wound‐healing efficiency of ≈10 mm 2 per day, which sets a benchmark among these noble‐metal‐free nanozyme‐based wound‐healing agents. Abstract : An atomic‐dispersion iron‐doped oxygen‐deficient molybdenum oxide MoO3− X bifunctional nanozyme, featuring with implanted peroxidase‐like, enhanced catalase‐like activity and unimaginably high aqueous dispersity has been developed for microenvironment‐adaptive ROS regulation for wound healing. The introduction of iron into MoO3− X synchronously stabilizing adsorption of OH and weakening the adsorption of O2, which sets a benchmark for timely antibacterial and efficient proliferation and remodeling.